Hubungan Usia dan Paritas dengan Kanker Payudara di Rumah Sakit Kebonjati Bandung - Yunita Sarah Nadeak (Pusat Riset dan Inovasi Nasional, 2023)
Breast cancer is a malignant tumor of the breast, lump or single mass often present in the upper outer quadrant region, this lump is hard and irregularly shaped and can be moved. Breast cancer as the most common type of cancer in women. In every year more than 250,000 new cases of breast cancer. The incidence of breast cancer in Putri Hijau Hospital Medan 2014-2022 was 43 cases. The purpose of this study was to determine the relationship between age and parity with breast cancer Kebonjati Bandung Hopital. This research was an Analytical Survey with Cross Sectional approach that is a research where the measurement of free variable and dependent variable is done in the same time. This study used the Total Population method to take a sample where the entire population amounted 43 cases of breast cancer. Techniques of data collection were secondary data that was taken from medical record of Kebonjati Hospital Bandung. Breast cancer stands out at the age of 40-50 years as many as 18 people (41. 9%) and in multiparous parity as many as 21 people (48. 8%). The results showed that the variable age ρ = 0. 036 and parity ρ = 0. 023 < 0. 05, it eans there is a significant relationship between age and parity with breast cancer. Conclusions in this study were respondents who are at high risk of developing breast cancer occurs at the age of 40-50 years and multiparity parity. For health workers are expected to provide health promotion and provide proper and prompt health services in breast cancer disease so that it can reduce mortality.